Preparation method and application of lignin carbon-based difunctional electro-catalytic material for oxygen reduction and oxygen evolution

By combining lignin with transition metal and ammonium chloride, nitrogen-doped lignin carbon materials were prepared, which solved the problem that existing electrocatalysts could not meet the dual functions of ORR-OER, and achieved efficient and stable zinc-air battery performance , improves the output power density and cycle stability of the battery.

CN119230849APending Publication Date: 2024-12-31NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341638.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing electrocatalysts cannot achieve suitable wetting, low cost, high efficiency, high stability and meet the dual functions of oxygen reduction and oxygen precipitation reaction (ORR-OER), limiting the output power density and stability of zinc-air batteries. .

Method used

Using a preparation method of lignin-carbon-based bifunctional electrocatalytic material, nitrogen doping with hydrophobicity and high specific surface area is prepared by combining lignin with transition metal and ammonium chloride, and calcining and freeze-drying treatment. The lignin carbon material regulates its porosity and wettability, forming a reaction interface where the three phases of gas/liquid/solid coexist, and improving catalytic performance.

Benefits of technology

A peak power density up to 212mW/cm2 and a specific capacity of 810mA·h/g1 were achieved, and a cyclic stability of 150h was maintained, significantly improving the performance of ORR and OER.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230849A_ABST
    Figure CN119230849A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a lignin carbon-based bifunctional electro-catalytic material for oxygen reduction and oxygen evolution, and belongs to the technical field of catalysts. The invention aims to solve the problems that the existing electrocatalyst cannot simultaneously realize proper wettability, low cost, high efficiency and high stability and cannot meet ORR-OER dual functions. The method comprises the following steps: 1, preparing a transition metal-lignin solution; 2, adding ammonium chloride and freeze-drying; and 3, high-temperature calcination. The positive electrode material is used as a positive electrode of a zinc-air battery and is used for oxygen reduction and oxygen evolution. The invention relates to preparation and application of the lignin carbon-based bifunctional electro-catalytic material for oxygen reduction and oxygen evolution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts. Background Art

[0002] In order to promote the healthy development of my country's new energy industry, optimize the energy structure and continuously improve the ecological environment, the development and utilization of biomass energy should be placed in an important position. To this end, it is urgent to increase the development and utilization of rich low-value biomass resources such as agricultural and forestry wastes. In this process, lignin, as a component mainly present in agricultural and forestry wastes, has become a challenge that researchers must face in terms of efficient conversion and high-value utilization. Lignin is not only the second largest natural organic polymer in nature after cellulose, but also the only renewable aromatic polymer in plants with a high carbon content. The world produces up to 150 billion tons of lignin through photosynthesis each year. At present, the main ways to obtain lignin in the market are the papermaking industry and the biomass refining industry, and the papermaking industry produces about 50 million tons of industrial lignin each year. However, only about 10% of it has been effectively utilized, and most of the rest are burned or directly discharged as low-value fuels, which not only causes a huge waste of resources, but also has an adverse impact on the environment. Therefore, exploring and implementing efficient and high-value utilization strategies for industrial lignin are of far-reaching significance for promoting my country's economic sustainable development, protecting the environment, and improving social benefits.

[0003] With the increasing shortage of energy supply and environmental pollution, the research on electrochemical energy storage and conversion systems has become more and more in-depth. In this field, zinc-air batteries have attracted much attention due to their high energy density, low cost, safety, and environmental protection. During the charge and discharge process of zinc-air batteries, the air cathode undergoes oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). However, due to the slow characteristics of the ORR-OER reaction kinetics, the battery produces a high overpotential in these reactions, which in turn affects the output power density and stability of the battery, limiting its commercialization process. At present, the best known ORR-OER electrocatalysts are Pt-based catalysts and Ru / Ir-based catalysts. However, the application of these precious metal-based catalysts is limited by high cost and insufficient stability. In addition, the ORR and OER reactions both involve gas, so an efficient reaction process requires a certain balance between the solid catalyst, liquid electrolyte, and gaseous reactants or products. In the ORR process, the hydrophobic microenvironment can accelerate the mass transfer of gaseous reactants to the active sites, and facilitate the rapid detachment of the generated bubbles to restore the active sites; on the contrary, in the OER process, the hydrophilic microenvironment is conducive to the contact between the active sites of the catalyst and the liquid electrolyte, thereby promoting the gas production reaction. Therefore, catalysts suitable for both ORR and OER need to have appropriate wettability to ensure both efficient transmission of gas to the catalyst and contact between the catalyst and the liquid electrolyte. However, existing electrocatalysts cannot simultaneously achieve appropriate wettability, low cost, high efficiency, high stability and meet the dual functions of ORR-OER. Summary of the invention

[0004] The present invention aims to solve the problem that existing electrocatalysts cannot simultaneously achieve suitable wettability, low cost, high efficiency, high stability and meet the ORR-OER dual functions, and further provide a preparation method and application of lignin carbon-based bifunctional electrocatalyst materials for oxygen reduction and oxygen evolution.

[0005] A method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution is carried out according to the following steps:

[0006] 1. Dissolve lignin in distilled water, then add a transition metal compound and stir evenly to obtain a transition metal-lignin solution;

[0007] The mass ratio of the lignin to the transition metal compound is 1:(0.1-0.4);

[0008] 2. adding ammonium chloride to the transition metal-lignin solution and stirring evenly, and then freeze-drying and grinding to obtain a lignin-based composite material;

[0009] The mass ratio of lignin to ammonium chloride in the transition metal-lignin solution is 1:(2-10);

[0010] 3. Under an inert atmosphere, the lignin-based composite material is calcined at high temperature, then cooled to room temperature, washed and dried to obtain a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution.

[0011] Application of a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution as a positive electrode of a zinc-air battery for oxygen reduction and oxygen evolution.

[0012] The beneficial effects of the present invention are:

[0013] 1. The present invention makes full use of the rich functional groups of lignin, skillfully combines transition metals with lignin, effectively anchors metal species, promotes the dispersion of catalyst metal sites, has a simple preparation process, a wide range of raw material sources, low cost, and can be mass-produced.

[0014] 2. The preparation method of the present invention utilizes the characteristics of lignin with high carbon content and extremely strong hydrophobicity to prepare lignin into a hydrophobic carbon material, and utilizes the characteristic that ammonium chloride releases a large amount of gas during pyrolysis. On the one hand, the porosity of lignin carbon is adjusted and the specific surface area of ​​the material is increased. On the other hand, the introduction of nitrogen species can increase the proportion of sp2 hybrid structure (pyridine nitrogen) in the material, thereby regulating the wettability of the lignin carbon material, further optimizing the local gas / liquid equilibrium around the catalytic site, and forming a reaction interface where gas, liquid and solid coexist on the catalyst surface, promoting gas diffusion on the electrode, thereby improving ORR and OER performance.

[0015] 3. The preparation method of the present invention uses ammonium chloride as a nitrogen source. The nitrogen-doped lignin carbon obtained by adjusting the carbonization temperature has a higher pyridinic nitrogen content, which is beneficial to the ORR performance. At the same time, nitrogen doping changes the electronic structure of carbon, which is beneficial to improving the catalytic activity and stability. The test results show that the catalytic performance of the electrocatalyst of the present invention is good. The half-wave potential of ORR is measured to be 0.86V at 10mA / cm 2 At this current density, the overpotential of OER is 296 mV.

[0016] 4. The transition metal-loaded lignin carbon-based electrocatalytic material obtained by the preparation method of the present invention can be used in the positive electrode of zinc-air batteries and has a high conductivity of up to 212 mW / cm 2 Peak power density, 810mA·h / g 1 The specific capacity and cycle stability of up to 150h.

[0017] Instruction Manual

[0018] Figure 1The scanning electron microscope images, nitrogen adsorption and desorption curves, and pore size distribution diagrams of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1, a is a scanning electron microscope image of FeNi3@NC, b is a scanning electron microscope image of FeNi3@C, c is a nitrogen adsorption and desorption curve, and d is a pore size distribution diagram;

[0019] Figure 2 The transmission electron microscopy image and energy dispersive X-ray spectrum of FeNi3@NC prepared in Example 1, a is the transmission electron microscopy image, and b is the energy dispersive X-ray spectrum;

[0020] Figure 3 A comparison diagram of the contact angles of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1 to water;

[0021] Figure 4 The absorption of underwater bubbles on FeNi3@NC prepared in Example 1;

[0022] Figure 5 The N1s XPS spectra of FeNi3@NC prepared at different carbonization temperatures in Examples 1 to 3 and the corresponding pyridinic nitrogen content comparison diagram, a is Example 1, b is Example 2, c is Example 3, and d is the comparison of pyridinic nitrogen content;

[0023] Figure 6 The ORR and OER electrochemical test results of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1, a is ORR, b is OER;

[0024] Figure 7 The performance comparison of zinc-air batteries, a is the charge and discharge polarization curve and power density curve of zinc-air batteries, b is the charge and discharge polarization curve and power density curve of zinc-air batteries at 10mA / cm 2 The constant current discharge curve of zinc-air battery at 5 mA / cm 2 The constant current charge / discharge cycle curve. DETAILED DESCRIPTION

[0025] Specific embodiment 1: This embodiment is a method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution, which is carried out in the following steps:

[0026] 1. Dissolve lignin in distilled water, then add a transition metal compound and stir evenly to obtain a transition metal-lignin solution;

[0027] The mass ratio of the lignin to the transition metal compound is 1:(0.1-0.4);

[0028] 2. adding ammonium chloride to the transition metal-lignin solution and stirring evenly, and then freeze-drying and grinding to obtain a lignin-based composite material;

[0029] The mass ratio of lignin to ammonium chloride in the transition metal-lignin solution is 1:(2-10);

[0030] 3. Under an inert atmosphere, the lignin-based composite material is calcined at high temperature, then cooled to room temperature, washed and dried to obtain a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution.

[0031] The beneficial effects of this embodiment are:

[0032] 1. This embodiment makes full use of the rich functional groups of lignin, cleverly combines transition metals with lignin, effectively anchors metal species, promotes the dispersion of catalyst metal sites, has a simple preparation process, a wide range of raw material sources, low cost, and can be mass-produced.

[0033] 2. The preparation method of this embodiment utilizes the characteristics of lignin with high carbon content and extremely strong hydrophobicity to prepare lignin into a hydrophobic carbon material, and utilizes the characteristic that ammonium chloride releases a large amount of gas during pyrolysis. On the one hand, the porosity of lignin carbon is adjusted and the specific surface area of ​​the material is increased. On the other hand, the introduction of nitrogen species can increase the proportion of sp2 hybrid structure (pyridine nitrogen) in the material, thereby regulating the wettability of lignin carbon material, further optimizing the local gas / liquid equilibrium around the catalytic site, and forming a reaction interface where gas, liquid and solid coexist on the catalyst surface, promoting gas diffusion on the electrode, thereby improving ORR and OER performance.

[0034] 3. The preparation method of this embodiment uses ammonium chloride as a nitrogen source. The nitrogen-doped lignin carbon obtained by adjusting the carbonization temperature has a higher pyridinic nitrogen content, which is beneficial to ORR performance. At the same time, nitrogen doping changes the electronic structure of carbon, which is beneficial to improving catalytic activity and stability. The test results show that the catalytic performance of the electrocatalyst of this embodiment is 0.86V for the half-wave potential of ORR at 10mA / cm 2 At this current density, the overpotential of OER is 296 mV.

[0035] 4. The transition metal-loaded lignin carbon-based electrocatalytic material prepared by the preparation method of this embodiment can be used in the positive electrode of zinc-air batteries and has a high conductivity of up to 212 mW / cm 2 Peak power density, 810mA·h / g 1 The specific capacity and cycle stability of up to 150h.

[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the lignin described in step 1 is one or a combination of alkali lignin, enzymatic lignin and organic solvent lignin. The rest is the same as specific implementation method 1.

[0037] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the transition metal compound in step 1 is one or a combination of iron nitrate, nickel nitrate, cobalt nitrate and copper nitrate. The rest is the same as specific implementation method 1 or 2.

[0038] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the volume ratio of the mass of lignin to distilled water in step 1 is 1 g: (10-20) mL. The rest is the same as specific embodiments 1 to 3.

[0039] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the freeze drying in step 2 is performed at a temperature of -30°C to -60°C for 24h to 36h. The rest is the same as specific embodiments 1 to 4.

[0040] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the inert atmosphere in step 3 is one or a combination of nitrogen, helium, neon, argon, krypton and xenon. The rest is the same as specific implementation examples 1 to 5.

[0041] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the high temperature calcination in step 3 is specifically carried out at a temperature of 600° C. to 1100° C. for 1 h to 6 h. The rest is the same as specific embodiments 1 to 6.

[0042] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the temperature is raised to 600° C. to 1100° C. at a heating rate of 3° C. / min to 10° C. / min. The rest is the same as specific embodiments 1 to 7.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the drying described in step 3 is carried out at a temperature of 10° C. to 103° C. for 1 h to 24 h. The rest is the same as specific embodiments 1 to 8.

[0044] Specific embodiment ten: This embodiment is an application of a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution, which is used as the positive electrode of a zinc-air battery for oxygen reduction and oxygen evolution.

[0045] The following examples are used to verify the beneficial effects of the present invention:

[0046] Embodiment 1:

[0047] A method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution is carried out according to the following steps:

[0048] 1. Dissolve lignin in distilled water, then add nickel nitrate and iron nitrate and stir evenly to obtain a transition metal-lignin solution;

[0049] The lignin is alkaline lignin; the mass ratio of the lignin to distilled water is 1 g:15 mL; the mass ratio of the lignin to nickel nitrate is 1:0.22; the mass ratio of the lignin to iron nitrate is 1:0.11;

[0050] 2. adding ammonium chloride to the transition metal-lignin solution and stirring evenly, then freeze-drying at -50°C for 24 hours, and finally grinding to obtain a lignin-based composite material;

[0051] The mass ratio of lignin to ammonium chloride in the transition metal-lignin solution is 1:5;

[0052] 3. Under a nitrogen atmosphere, the temperature of the lignin-based composite material was raised to 800°C at a heating rate of 5°C / min, and then calcined at 800°C for 2 hours, then cooled to room temperature, washed with distilled water, and finally dried at 60°C for 8 hours to obtain a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution, named FeNi3@NC.

[0053] Embodiment 2: This embodiment is different from Embodiment 1 in that: in step 3, the high temperature calcination is performed at 900° C. for 2 h. The rest is the same as Embodiment 1.

[0054] Embodiment 3: This embodiment is different from Embodiment 1 in that: in step 3, the high temperature calcination is carried out at a temperature of 1000° C. for 2 h. The rest is the same as Embodiment 1.

[0055] Comparative Example 1: This comparative example is different from Example 1 in that the addition of ammonium chloride in step 2 is eliminated, and the transition metal-lignin solution is directly freeze-dried and ground in step 2; and in step 3, a lignin carbon-based bifunctional electrocatalytic material is obtained, named FeNi3@C. The rest is the same as Example 1.

[0056] Figure 1The scanning electron microscope images, nitrogen adsorption and desorption curves, and pore size distribution diagrams of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1, a is a scanning electron microscope image of FeNi3@NC, b is a scanning electron microscope image of FeNi3@C, c is a nitrogen adsorption and desorption curve, and d is a pore size distribution diagram; As can be seen from Figures a and b, FeNi3@NC shows a relatively uniform pore structure, while Figure FeNi3@C shows a relatively flat structure, which indicates that ammonium chloride can effectively regulate the microstructure of lignin carbon and obtain a uniform pore structure. As can be seen from Figures c and d, Example 1 has 504.5m 2 g -1 The specific surface area is much larger than that of the comparative example 109.1m 2 g -1 The specific surface area of ​​FeNi3@NC and FeNi3@C is mainly mesopores with a diameter of 2nm to 4nm.

[0057] Figure 2 The transmission electron microscope image and energy dispersive X-ray spectrum of FeNi3@NC prepared in Example 1, a is the transmission electron microscope image, and b is the energy dispersive X-ray spectrum. From the transmission electron microscope image, it can be seen that the lignin carbon material is coated with nickel-iron metal particles. From the energy dispersive X-ray spectrum, it can be seen that Fe, Ni, N, C, and O are uniformly distributed in the electrocatalyst FeNi3@NC.

[0058] Figure 3 The contact angle comparison diagram of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1 to water; the results show that the catalyst FeNi3@C has a large contact angle of up to 150.37°, indicating that it has ultra-high hydrophobicity. However, an overly hydrophobic microenvironment will reduce the contact between the active site and the liquid electrolyte, and limit the number of protons that can participate in the reaction and the ionic conductivity, thereby having a negative impact on the catalytic performance. After nitrogen doping, the catalyst FeNi3@NC has a contact angle reduced to 104.29°, which can ensure the contact between the electrolyte and the active site while being hydrophobic, and the constructed gas / liquid / solid three-phase interface can effectively improve the catalytic activity.

[0059] Figure 4 The absorption of underwater bubbles on FeNi3@NC prepared in Example 1; it can be seen from the figure that the bubbles are completely absorbed on the catalyst surface in just 9 ms, indicating that although the contact angle of the catalyst FeNi3@NC decreases, it still has good gas affinity, which is beneficial to the mass transfer of gaseous reactants to the active sites.

[0060] Figure 5Comparison of the N1s XPS spectra of FeNi3@NC prepared at different carbonization temperatures in Examples 1 to 3 and the corresponding pyridinic nitrogen content, a is Example 1, b is Example 2, c is Example 3, and d is the comparison of pyridinic nitrogen content; from ac, it can be seen that with the increase of temperature, the proportion of pyridinic nitrogen decreases from 34.99% at 800°C to 14.56%.

[0061] Catalyst ORR and OER electrochemical performance test: FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1 were tested on a CHI760E electrochemical workstation, respectively. 5 mg of catalyst was added to 980 μL of ethanol solution and 20 μL of 5% Nafion solution by mass, and then the mixture was continuously ultrasonicated to form a uniform catalyst ink, and 20 μL of catalyst ink was dropped onto a glassy carbon electrode for testing. The test method adopted a three-electrode system, with a glassy carbon electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. ORR tests were performed in an oxygen-saturated 0.1M potassium hydroxide aqueous solution at room temperature, and OER tests were performed in a 1M potassium hydroxide aqueous solution at room temperature.

[0062] Figure 6 The ORR and OER electrochemical test results of FeNi3@NC prepared in Example 1 and FeNi3@C prepared in Comparative Example 1, a is ORR, b is OER; As can be seen from the figure, in the ORR electrochemical test, FeNi3@NC has a half-wave potential of 0.86V, which is significantly higher than that of Comparative Example 1 (0.71V); in the OER electrochemical test, at 10mA / cm 2 The overpotential of FeNi3@NC was measured to be 296 mV, which is better than the performance of comparative example 1 (337 mV).

[0063] Catalyst zinc-air battery performance test: FeNi3@NC or 20% Pt / C+RuO2 (purchased) prepared in Example 1 was coated on carbon paper (loading amount was 1 mg / cm 2 ) and as the air cathode (positive electrode), a polished zinc sheet (0.3 mm thick, 1 cm 2 ) was used as the anode (negative electrode), and the electrolyte was a mixed aqueous solution of 6M KOH and 0.2M Zn(OAc)2 to obtain zinc-air batteries FeNi3@NC and 20% Pt / C+RuO2, respectively.

[0064] Figure 7 The performance comparison of zinc-air batteries, a is the charge and discharge polarization curve and power density curve of zinc-air batteries, b is the charge and discharge polarization curve and power density curve of zinc-air batteries at 10mA / cm 2 The constant current discharge curve of zinc-air battery at 5 mA / cm 2The constant current charge / discharge cycle curve is shown in Figure a. As shown in Figure 1, the zinc-air battery with FeNi3@NC catalyst coated on the positive electrode has a charge / discharge rate of 212 mW / cm 2 The power density is higher than that of the zinc-air battery prepared with 20% Pt / C-RuO2 (90 mW / cm 2 ). As shown in Figure b, the zinc-air battery with the positive electrode coated with FeNi3@NC catalyst has a high current density of up to 810 mA·h / g 1 The specific capacity is significantly higher than that of the zinc-air battery prepared with 20% Pt / C-RuO2 (707 mA·h / g 1 ); As shown in Figure c, the zinc-air battery with the positive electrode coated with FeNi3@NC catalyst showed excellent durability within 150 h without obvious signs of attenuation, while the zinc-air battery prepared with 20% Pt / C-RuO2 had a limited cycle time of only 69 h.

Claims

1. A method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution, characterized in that It is carried out in the following steps:

1. Dissolve lignin in distilled water, then add a transition metal compound and stir evenly to obtain a transition metal-lignin solution; The mass ratio of the lignin to the transition metal compound is 1:(0.1-0.4); 2. adding ammonium chloride to the transition metal-lignin solution and stirring evenly, and then freeze-drying and grinding to obtain a lignin-based composite material; The mass ratio of lignin to ammonium chloride in the transition metal-lignin solution is 1:(2-10); 3. Under an inert atmosphere, the lignin-based composite material is calcined at high temperature, then cooled to room temperature, washed and dried to obtain a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution.

2. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The lignin described in step 1 is one of alkali lignin, enzymatic lignin and organic solvent lignin, or a combination of several of them.

3. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The transition metal compound described in step 1 is one of iron nitrate, nickel nitrate, cobalt nitrate and copper nitrate, or a combination of several thereof.

4. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The volume ratio of the lignin mass to distilled water described in step 1 is 1 g: (10-20) mL.

5. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The freeze drying described in step 2 is specifically freeze drying at a temperature of -30°C to -60°C for 24h to 36h.

6. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The inert atmosphere described in step 3 is one of nitrogen, helium, neon, argon, krypton and xenon, or a combination of several of them.

7. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The high temperature calcination in step 3 is specifically calcining at a temperature of 600° C. to 1100° C. for 1 h to 6 h.

8. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 7, characterized in that The temperature is raised to 600°C to 1100°C at a heating rate of 3°C / min to 10°C / min.

9. The method for preparing a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution according to claim 1, characterized in that The drying described in step 3 is specifically drying at a temperature of 10° C. to 103° C. for 1 h to 24 h.

10. Use of a lignin carbon-based bifunctional electrocatalytic material for oxygen reduction and oxygen evolution prepared as claimed in claim 1, characterized in that It serves as the cathode in zinc-air batteries for oxygen reduction and oxygen evolution.